2016
DOI: 10.1111/jep.12606
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist–physician collaborative care model for patients with uncontrolled type 2 diabetes in Brazil: results from a randomized controlled trial

Abstract: The results suggest that the collaborative care model proposed is feasible and more effective than the usual care in the reduction and individualized control of A1C levels in patients with uncontrolled type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 30 publications
4
91
0
1
Order By: Relevance
“…(32) It was not possible to determine whether lack of specific tools such as Pharmacotherapy WorkUp for drug-related problems might have contributed to heterogeneity, because only two studies reported the use of this tool for that specific purpose. (30,35) Even if all 15 studies selected for systematic review had been included in this meta-analysis, results would still probably be similar. Significant heterogeneity may have reflected differences in inclusion criteria between trials.…”
Section: Triglyceridesmentioning
confidence: 98%
See 3 more Smart Citations
“…(32) It was not possible to determine whether lack of specific tools such as Pharmacotherapy WorkUp for drug-related problems might have contributed to heterogeneity, because only two studies reported the use of this tool for that specific purpose. (30,35) Even if all 15 studies selected for systematic review had been included in this meta-analysis, results would still probably be similar. Significant heterogeneity may have reflected differences in inclusion criteria between trials.…”
Section: Triglyceridesmentioning
confidence: 98%
“…(34) As regards detection bias, only one study reported blinding of raters, who were therefore unaware of groups being evaluated. (35) The remaining studies were thought to have unclear risk of bias, given measures employed to assess clinical outcomes were not described.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7] Studies have proved that a better collaboration between healthcare providers and pharmacists has led to safer, more effective and less costly drug therapies. [8][9][10] In 2011, a study conducted by Zidane et al 10 in our institute, which aimed to investigate the physicians' perceptions and expectations from their experiences with the pharmacists at Hamad Medical Corporation (HMC), the largest governmental healthcare organization in Qatar, found that physicians were comfortable working with pharmacists and had high expectations of pharmacists in performing their duties. However, physicians reported a poor experience with clinical pharmacists, who infrequently informed them about the effectiveness of alternative drugs, patients experiencing problems with prescribed medications, and who took personal responsibility to resolve any drug-related problem.…”
Section: Introductionmentioning
confidence: 99%